Shanti Lal Kayastha A Humanist amongst Human Geographers - Alam, Sarfaraz (National Geographical Journal of India, 2022)
Prof. Shanti Lal Kayastha, a widely-acclaimed geographer and environmental scientist and a doyen of Indian Geography, was a wonderful confluence of multiple and to some extent divergent traditions- of the Himalayas and the Ganga Valley, of Banaras and Lahore, of Aligarh Muslim University and Banaras Hindu University, of colonial and post-colonial India. Born and spent his childhood in the Himalayan town of Kangra (then a part of Punjab State, but presently a part of Himachal Pradesh), he mostly lived and worked at Banaras Hindu University, situated on the bank of the river Ganga. He was one of those distinguished geographers from the Indian Sub-continent who studied as well as taught in both colonial and post-colonial India. He has the distinction of being one of those exceptional geographers from the Indian sub-continent who had studied as well as taught geography in both India and Pakistan. Prof. Kayastha was the strongest link between Aligarh and Banaras Schools of Geography. In his passing away, one of the most authentic connect in the Geographical Schools of Indian Sub-continent has been severed. It is precisely for these reasons that the mapping of academic trails of Prof. S.L. Kayastha is attempted here.